PERISTILAHAN PENUNJUK WAKTU DAN TEMPAT DALAM BAHASA MELAYU DIALEK SAMBAS - Rahmawati, Desi; Patriantoro, Patriantoro; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractTime and place indicator in Malay Sambas dialect is one of Sambas community's wealth in language field. Time and place indicator used by the Sambas Malay community come from the neighborhood around as the former of those terms. The purpose of this research is to know the form, the lexical meaning, the cultural meaning, and the semantic function. The method used in this research was descriptive and using ethnolinguistic approach. The techniques used in this study that was interviews, proficient, referent, and record. Data collection tool in the form of recorder and stationery. Based on the research conducted, the data collected amounted to 118 terminology of time and places in Sambas dialect Malay Language. The time and place terminologies in this research consists of two forms, those are the word in the form of monomorphemic and polymorphism and phrase. The monomorphemic terminology is 38 words. The lingual unit in the form of a polymorphism of affixation consisting of 24 terms. Lingual units in the form of phrases amounting to 38 terms. The term that has lexical meaning amounts to 79 terms and which has a cultural significance of 88 terms and that terms has the function sematis amounted to 118.Keywords: terminology, time indicator, place indicator, Language of Sambas Malay Society.